Exploring Predictors of Development and Career Planning Among TVET Educators - Zakaria, Anies Faziehan; Hanapi, Zaliza; Mustafa, Mohd Syafiq Syazwan; Ma'arof, Muhammad Izzat Nor (Journal of Technical Education and Training, 2022)
Career planning and development a key factor that provides added value to career sustainability. Career development approaches have recently changed due to the fast-paced global change, competitive industry needs, demands, and global education trends. Traditionally, it was the responsibility of an institution to guarantee that its educators possessed the skills necessary to achieve its long-term objectives. Currently, however, educators should be accountable for their career growth. Therefore, a survey was conducted to discover predictors of development and career paling for TVET educators (n = 141). A multiple regression analysis was conducted for all sets of career planning variables such as career aspirations (88.48%), personal aspirations and drive (85.93%), current competency (86.00%), current learning and development opportunities (82.05%), and company support 87.45%) is measured. This study found changes in the predictor, personal aspirations and drive, current competency, current learning and development opportunities, and organization support are significantly associated with changes in career aspiration. The majority of TVET educators are aware and willing to improve their knowledge and skills to meet the standard of current changes in TVET education needs and demands. The finding indicated that a proven technique for meeting organizational and personnel demands includes creating career routes that allow TVET educators to comprehend their options for advancement within the institution and collecting information to assess their abilities for career relevancy and sustainability.